AB0730 RECLASSIFICATION INTO VERY HIGH CARDIOVASCULAR RISK AFTER CAROTID ULTRASOUND IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS. (June 2019) - Quevedo-Abeledo, Juan Carlos; Rueda-Gotor, Javier; Genre, Fernanda; Corrales, Alfonso; Hernández-Hernández, Vanessa; Delgado-Frías, Esmeralda; Montelongo, Sonia Peña; Rodríguez-Lozano, Carlos; González-Gay, Miguel a.; Ferraz-Amaro, Iván
Abstract : Background: Axial spondyloarthritis (a-SpA) are associated with an increase in cardiovascular (CV) morbidity and mortality. Subclinical atherosclerosis, in the form of carotid plaques, is more frequent in this patients than in healthy controls. How the presence of carotid plaque affects the reclassification of CV risk in a-SpA has not been study before. Besides, it is not known if this reclassification can be explained by characteristics related to the disease. Objectives: To analyze whether the reclassification of CV risk after performing carotid ultrasound is more frequent in this patients compared to controls and whether this reclassification can be explained by characteristics related to the disease such as activity, functional damage or metrology scores. Methods: Study of 343 a-SpA patients according to aSAS criteria and 177 controls with no previous history of CV events, diabetes or chronic kidney disease. The clinical characteristics and risk profile were analyzed in patients and controls by SCORE. The presence of plaques and intima-media thickness (cIMT) was determined by carotid ultrasound. The differences in the presence of reclassification between patients and controls and the factors associated with this in patients with a-SpA, were analyzed by multivariated regression analysis. Results: Patients with a-SpA compared to controls disclosed a higher presence of hypertension (p=0.000), dyslipidemia (p=0.000) and smoking (p=0.000). Consequently, patients also showed a significantly higher SCORE than controls (0.6 IQR [0.1-2.0] vs. 0.1 [0.0-0.4], p=0.000). The presence of carotid plaque (36% vs. 25%, p=0.010) and cIMT (0.641 ± 0.121 vs. 0.602 ± 0.115 mm, p=0.001) were higher in patients compared to controls. Moreover, the possibility of being reclassified into very high-risk category after ultrasound was superior in patients (34% vs 25%, p=0.037). The possibility of being reclassified was associated, both in patients and controls, with an older age, male sex, abdominal circumference, hypertension and dyslipidemia. Contrary, body mass index and serum levels of cholesterol, LDL cholesterol and atherogenic index only showed association with reclassification in controls. The effect of each factor associated with reclassification in patients and controls was compared by the addition of interaction factors in the regression model. In this sense, age (beta coef 2.74 [IC95% 1.34-5.62] in controls vs. beta coef 0.63 (95% CI 0.40-0.99) in patients, interaction p=0.001) and serum LDL cholesterol levels (beta coef 1.03 [IC95% 1.02-1.04] vs. beta coef 1.00 [0.99-1.01], interaction p=0.002), cholesterol and atherogenic index, showed a greater effect in controls than in patients. The reclassification in patients with a-SpA was associated with a higher aSDAS-PCR (2.2 ± 1.0 VS. 2.5 ± 1.0, p=0.041), BASFI (3 [1-5] vs. 4 [2-7], p=0.000) and BASMI scores (2 [1-4] vs. 4 [2-5], p=0.000). However, these differences were lost when they were analyzed adjusting for CV risk factors. Conclusion: Patients with a-SpA are more likely to be reclassified into very high-risk after carotid ultrasound compared to controls. Traditional CV risk factors have less effect on this reclassification in patients than in controls. The activity, functionality and metrology scores of the a-SpA have a univariate positive relationship with this reclassification. Disclosure of interests: Juan Carlos Quevedo-Abeledo: None declared, Javier Rueda-Gotor: None declared, Fernanda Genre: None declared, alfonso Corrales: None declared, Vanessa Hernández-Hernández: None declared, Esmeralda Delgado-Frías: None declared, Sonia Peña Montelongo: None declared, Carlos Rodríguez-Lozano: None declared, Miguel a González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Iván Ferraz-Amaro: None declared